2021
DOI: 10.3389/fsurg.2021.769658
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Factors for Surgical Failure in Malignant Bowel Obstruction and Peritoneal Carcinomatosis

Abstract: Introduction: Patients with peritoneal metastasis frequently develop malignant bowel obstruction (MBO). Medical palliative management is preferred but often fails. Conversely, the role of palliative surgery remains unclear and debated. This study aims to identify patients who could benefit from invasive surgical interventions and factors associated with successful surgical palliation.Materials and Methods: In this retrospective study, 98 consecutive patients who underwent palliative surgery for MBO over 5 year… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 24 publications
(24 reference statements)
0
12
0
Order By: Relevance
“…[2][3][4] MBO from PC is managed in a multidisciplinary setting and may involve palliative considerations, given it often reflects disease progression and the advanced nature of a patient's metastatic disease. 5 Surgical interventions such as palliative diverting ostomy, bowel resection, and bypass are invasive treatment options and are only appropriate in a subset of patients given the high associated morbidity and mortality. 5,6 Other management options include medical treatments such as corticosteroids, antiemetics, and antisecretory medications.…”
Section: Introductionmentioning
confidence: 99%
“…[2][3][4] MBO from PC is managed in a multidisciplinary setting and may involve palliative considerations, given it often reflects disease progression and the advanced nature of a patient's metastatic disease. 5 Surgical interventions such as palliative diverting ostomy, bowel resection, and bypass are invasive treatment options and are only appropriate in a subset of patients given the high associated morbidity and mortality. 5,6 Other management options include medical treatments such as corticosteroids, antiemetics, and antisecretory medications.…”
Section: Introductionmentioning
confidence: 99%
“…On the contrary, infiltration of the root of the small bowel mesentery and extensive small bowel disease that could leave short bowel syndrome after resection are potential contraindications for primary cytoreduction [ 3 ]. Furthermore, bowel obstruction complicates a significant proportion of patients with peritoneal carcinomatosis (PC), while as high as 50% of them presented with the recurrent disease even after complete cytoreduction [ 4 ]. Bowel obstruction can be due to either infiltration of the bowel and mesentery by the primary tumor or secondary due to the compression of the bowel from the primary lesion [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, bowel obstruction complicates a significant proportion of patients with peritoneal carcinomatosis (PC), while as high as 50% of them presented with the recurrent disease even after complete cytoreduction [ 4 ]. Bowel obstruction can be due to either infiltration of the bowel and mesentery by the primary tumor or secondary due to the compression of the bowel from the primary lesion [ 4 ]. Obstruction can also be caused by the presence of cancer adhesions and carries a grim outlook.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies showed that presence of poor performance status, pain, exertional shortness of breath, cognitive impairment, ascites, palpable masses in abdomen and pelvis, poor nutritional status, low albumin, liver failure, multifocal obstruction, and proximal MBO correlated with dismal survival. [16][17][18][19][20][21][22][23] Moreover, a recent retrospective review identified CT findings of ascites, mesenteric disease, and dilated bowel loop wall thinning as poor prognostic indicators. 24 Retrospective analyses have shown that systemic chemotherapy after the development of MBO is associated with superior survival, irrespective of whether patients were treated medically or surgically for MBO.…”
mentioning
confidence: 99%